Ocular Behçet disease and COVID-19. Issue 2 (March 2022) - Accorinti, Massimo; Manni, Priscilla; Sampalmieri, Lorenzo; Saturno, Maria Carmela
Purpose: to study in patients with Behçet disease and ocular involvement (OBD) the presence of SARS-CoV-2 infection and its influence on the course of OBD. Methods: all the patients with OBD living in Lazio, one Italian region, and attending the Uveitis center of the Sapienza University of Rome were included in the study. Results: SARS-CoV-2 infection was found in 12.3% of 54 patients with OBD and in 3.84% of Lazio inhabitants (p = 0.001, OR 3.51), and it was unrelated to the use of immunosuppressive drugs. COVID-19 symptoms in OBD patients were mild, with one patient only requiring hospitalization for interstitial pneumonia. None of the SARS-CoV-2 infected patients presented any uveitis relapses during the infection and in a subsequent median follow-up of 6 months. Conclusion: OBD seems to be a risk factor for developing SARS-CoV-2 infection. Usually this infection has a mild course and does not impact negatively on the course of uveitis.